Analytical and experimental solution of vibrations of a system of bound bodies - Cernohlavek, Vit; Svoboda, Martin; Sterba, Jan; Chalupa, Milan; Sapieta, Milan (Manufacturing Technology Journal, 2020)
The article deals with analytical and experimental solution of vertical oscillations of a mechanical system of bound bodies. The content of the article is to perform an analytical solution of the vertical oscillation of a system of bodies using the computer program MathWorks Matlab and MS Excel. Furthermore, an experimental investigation on a laboratory model of a mechanical system of the same parameters was proved. The aim of the work was to compare the analytical solution with the experimental method and to check the accuracy and applicability of analytical methods for the solved mechanical system.
Keywords: Vibration; Experiment; Passenger car; Analytical solution; Vehicle model